Plasticidade fenotípica de quatro espécies arbóreas na alocação de biomassa e de características funcionais foliares em resposta a diferentes condições ambientais - Vicente, Caroline Pardi (Universidade Federal de São Carlos, 2022)
Forest degradation is characterized by the loss of biomass production, resilience, and resistance of the ecosystem. The level of degradation of these ecosystems varies greatly between degraded areas, generating a great variability in environmental conditions, which compromises the predictability regarding the survival and growth speed of plants reintroduced in forest restoration projects. Several plant species have a wide geographic distribution and can occur in places with different environmental conditions above and below the ground. The morphological and physiological characteristics of plants, which are related to resource use and conservation, may vary with different abiotic conditions and resource availability. This study experimentally evaluated the effect of soil fertility and light availability under nursery and field conditions on the allocation of biomass between aerial parts (leaves and branches), root parts (thick and thin roots) and six functional characteristics of plants: leaf area, specific leaf area, leaf dry matter content, leaf thickness, root mass fraction and relative growth rate, after the first four months of planting. We selected four tree species commonly used in forest restoration, namely Colubrina glandulosa Perkins (Rhamnaceae), Hymenaea courbaril L. (Fabaceae), Myroxylon peruiferum L. f. e Pterogyne nitens Tul. (as três, Fabaceae). In the nursery, we evaluated the effect of fertilization at three levels: the addition of low or high amounts of mineral nutrients (NPK), composed of nitrogen (N), phosphorus (P) and potassium (K), and the addition of organic matter to the soil. All fertilization treatments were carried out in full sun and in 75% shading conditions to evaluate the effect of light in conjunction with the effect of fertilization. We also evaluated the response of these plants when introduced in the field, in a deforested area adjacent to a fragment of remaining riparian forest, but with high fertility. The addition of NPK mineral fertilizer in the soil of the bags resulted in higher values of P and K, but not of N, the addition of organic matter resulted in higher values of cation exchange capacity, saturation of pH and N bases in the soil. In all species, plants reached higher biomass in the nursery under high light intensity (full sun) and lower biomass in the field. In general, plants tended to allocate more biomass to leaves and less to fine roots when grown in full sun. The functional characteristics of the plants of the four species responded similarly to different conditions of light, nutrient availability and the field. Light availability strongly influenced the functional attributes of all species, with plants grown in shade showing higher values of specific leaf area and lower values of leaf dry matter content and leaf thickness, thus producing softer and thinner leaves. In the field, plants tended to produce smaller leaves, which may have been a response to water stress. Our results showed that within the same species, plants are able to adjust to low light conditions, forming leaves that are more efficient in light interception, characteristics associated 9 with a more acquisitive strategy, within the foliar economy spectrum model, and when grown in full sun, the plants tended to produce harder and thicker leaves, and therefore longer lasting, which is characteristic of more conservative strategies. The type of fertilization had a little or neglectable effect on the biomass production and the functional attributes of the plants. Plants in the field tended developing leaves with a smaller area, probably as a strategy to reduce the effects of water stress due to the long drought that occurred throughout the time of the experiment. This study demonstrated that all species are quite plastic and that they responded similarly to the availability of light and water, but that the variation in functional attributes in response to environmental conditions was not enough to compensate for the extremes of water and light deficit. Therefore, the functional attributes may reflect the different conditions of resource availability above and below the ground in degraded areas, and the study of the phenotypic plasticity of plants may help to understand the trajectories of plant communities, through greater predictability of biomass production and management strategies in forest restoration projects.
Phenotypic plasticity of four tree species in the biomass allocation and leaf functional characteristics in response to different environmental conditions
Keywords: Fertilidade de solo; Luminosidade; Crescimento de plantas; Soil fertility; Luminosity; Plant growth; CIENCIAS BIOLOGICAS::ECOLOGIA